Get Better at Flatter A Guide to Shaping and Leading Organizations with Less Hierarchy - Reitzig, Markus (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
When should organizations think about adopting a flat structure? And what does it take to make it work? Is it even the silver bullet that we've been told it is? Often we have heard about how businesses should organize in non-traditional ways to succeed in today's world: be 'agile', or adopt approaches such as 'holacracy,' 'RenDanHeYi' or 'scrum'. But what do these concepts actually mean? Are they even helping us to custom-tailor flat structures to our needs? Leading expert, Markus Reitzig, provides a no-holds barred account of flat organizational structures, taking the good with the bad and asking the reader to balance the opportunities and challenges that come with less hierarchical structures. He explains that there are many types of flat organizations, and that they may only be better than traditional companies in some instances, and only when the company picks the right structure given its goal and its people. Taking an evidence-based approach to the advantages and disadvantages of decentralizing, this book offers a unique, practical guide for managers. You'll learn how to formulate realistic goals with fewer hierarchical layers, where to decentralize, whom to recruit and how to treat your staff. This is an indispensable guide for anyone who wants to figure out how to work with flat organizational structures, and whether 'flat' may even be right for them.
Part 1: Why Flat Structures Work at All -- Chapter 1: What does it mean to move towards a "flatter" structure? -- Chapter 2: What managers can effectively and efficiently delegate -- Chapter 3: Why would employees ever assume extra work in a decentralized organization? -- Part 2: What Managers Can Do to Make Flat Structures Work Well -- Chapter 4: What type of persons should you take on the journey? -- Chapter 5: How to enforce and foster effective self-organization? -- Chapter 6: How to design the playing field for efficient quasi-decentralization? -- Part 3: When, Why, and How Flat Structures Can Beat Traditional Hierarchies -- Chapter 7: When can flat structures beat more centralized ones? -- Chapter 8: Where does a flat structure reach its limits? -- Chapter 9: The guide(s) to successful decentralizing -- Part 4: Test Your Understanding -- Chapter 10: Delayering the hierarchical firm-The case of Borek -- Chapter 11: Flat growth-The case of WirDesign -- Chapter 12: Flat fads or more? From a as in "agile" to z as in "zi zhu jing ying ti".
Keywords: Strategic planning; Leadership; Industrial organization; Business Strategy and Leadership; Organization